Phenolics, acyl galactopyranosyl glycerol, and lignan amides from Tetragonia tetragonioides (Pall.) Kuntze - Choi, Hwan Seong; Cho, Jeong-Yong; Jin, Mi Rim; Lee, Yu Geon; Kim, Seon-Jae; Ham, Kyung-Sik; Moon, Jae-Hak (Food science and biotechnology, 2016)
Eleven antioxidative compounds, including five lignin amides, were isolated from the aerial part of Tetragonia tetragonioides (New Zealand spinach) using 1,1-diphenyl-2-picrylhydrazyl radicalscavenging assay-guided purification. The structures were determined by nuclear magnetic resonance and electrospray ionization-mass spectroscopy. These compounds were identified as methyl linoleate ( 1 ), methyl coumarate ( 2 ), methyl ferulate ( 3 ), 1-O-stearoyl-3-O-β-D-galactopyranosyl-sn-glycerol ( 4 ), 1-O-caffeoyl-β-D-glucopyranoside ( 5 ), N-trans-caffeoyltyramine ( 6 ), cannabisin B ( 7 ), cannabisin A ( 8 ), Ntrans-feruloyltyramine ( 9 ), N-cis-feruloyltyramine ( 10 ), and N-trans-sinapoyltyramine ( 11 ). Compounds 1 , 2 , 4 , 5 , and 8 - 11 were isolated for the first time from this plant.